PETA KAJIAN PENDIDIKAN ISLAM PADA BERKALA ILMIAH DI IAIN MATARAM - Saparudin, Saparudin (LP2M IAIN Mataram, 2013)
The amount of research publication has been increasing, especially in Islam education area, in one side it can be made by high intellectual dynamics indicator in IAIN Mataram. But on the other side, map of the dynamics isnât yet read clearly in study object aspect, used approach, and also conducted study type. This condition, can implicate its direction and policy of development the Islamic education. To comprehend the mentioned, the method used is bibliography research (research library), include the analysis contents. Result of research show: firstly, object study aspect, study of Islamic education at periodically in IAIN Mataram which dominant express the philosophy aspect or idea of education of Islam as study object; secondly, its study object, from study type, the concept Islamic education has publicized Islam is periodically in IAIN Mataram, showing still its strength in theoretical study, include the field research, and library research; Third, parallel both aspect above, showing from applied the study approach, the tendency of study pattern education of Islam the lecturer of IAIN Mataram, can divide in a few pattern: (a) Pragmatic pattern, for having the adoptive character and also justificative; ( b) Idealist pattern, the study of al-Qurâan and Hadits and classic idea in more pre-eminent position to explain (non replying) a number of aspect / problem of Islamic education Islam; (c) Elective pattern (alliance of idealist pattern and pragmatic pattern); and (d) Empiric descriptive pattern.